Developement of Diagnosis and Recommentation Integrated System - Sreekumaran V (Department of Agronomy, College of Horticulture, 1998)
An investigative analysis was undertaken during 1993-96 to work out an objective and effective technology for nutritional management of black pepper based on cause and effect relationship. A critical and comparative evaluation of the available methods in this connection, viz. critical level concept, DRIS concept and management based on soil test data, soil analysis was envisaged. Approved standard procedures m estimating soil available and plant contents of nine elements, viz. N P K Ca Mg S Fe Zn and Mn and standard statistical methods were used in the study. A total of 1200 plants aged 14 years maintained at RARS, Ambalavayal were used as the test material in the study. A non-genic variability in yield ranging from 0.16 to 13.8 kg plant-1 was manifested by tile crop which indicated that variability shall be bridged upwards through managerial techniques. The range of available status of the elements in the soil analysis was very high. The lowest range of 0.9 to 4.5 ppm and the highest range of 144 to 1324 ppm were recorded by Zn and Ca, respectively. Soil pH ranged from 4.3 to 6.8. These were at the individual plant level. Foliar content as well as the range of the elements were much less and did not exactly related to soil available contents. Results also indicated that elements showed significant and specific interactions among themselves which varied with the elements. The pattern and magnitude of interactions at soil and plant level were different.